Community health workers perception about prenatal care - Reibnitz Schmitt, Kenya; Pedroso Canever, Bruna; Mattia, Daiana de; Virtuoso, Ariane Maccarini; Cartana Fontoura, Maria do Horto; Coelho Amestoy, Simone; Trindade, Letícia Lima (Investigación y Educación en Enfermería, 2011)
Objective. To describe the perception community health workers (CHW) have about prenatal care. Methodology. Convergent-care and qualitative study, carried out following the Paulo Freire’s pedagogical principles. The perceptions about difficulties found in the development of health care promotion activities of 15 community health workers who support prenatal care, were studied in a health institution of Santa Catalina (Brazil) between March and May of 2009. With a previous informed consent the community health workers participated in 6 workshops, in which their perceptions about knowledge and behaviors in prenatal care were evaluated using the policies of basic care of the health ministry. Data were categorized using the thematic analysis by Minayo. Results. Three categories emerged: previous knowledge, actions built by the CHW and teamwork-supportive work. Conclusion. CHW have previous knowledge about prenatal care, however it is not enough for them to understand and assess the effectiveness of their actions.